The importance of positive relationships for coaches' effectiveness and well-being - Davis, L.; Jowett, S.; Sörman, D. (International Sport Coaching Journal, 2023)
The present study investigated the role of quality coach-athlete relationships and coaching efficacy on coaches` well-being and performance. We examined whether coaches` direct and meta-perspectives of the coach-athlete relationship quality predicted dimensions of coaches` efficacy, hedemonic and eudaimonic well-being, and coach-related performance. A total of 233 male and female Swedish coaches from various team and individual sports completed the Coach-Athlete Relationship Questionnaire, the Coaching Efficacy Scale, Positive and Negative Affect Scale, Subjective Vitality Scale, and a one-single item developed to measure perceived coach performance. Structural equation modelling analyses revealed that quality coach-athlete relationships as defined by closeness, commitment, and complementarity associated with all four dimensions of coach efficacy. While coach-athlete relationship quality was linked with coaches` positive affect, vitality, and satisfaction with coaching performance, only the motivational dimension of coach efficacy was associated with indicators of coach well-being and coach-related performance. Further analyses showed that the motivational dimension of coach efficacy explained the link between coach-athlete relationship quality, well-being, and coach-related performance. Overall, the findings extended the coach efficacy model by investigating the coach-athlete relationship as a predictor and coach well-being as an outcome. Our findings emphasize the importance of relationships for coaches` efficacy and well-being.